Il campione biologico di unidentified person. Profili di sistema (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The essay analyses the discipline applicable to the biological sample belonging to an unidentified person. Considering the provisions applicable to the specific case, the paper verifies whether the biological sample can be qualified as a «bene giuridico» under article 810 of the Italian Civil Code. Concluding remarks concern the effects that the attribution of identity to a person deceased in ancient times may have on limitation period in paternity suits.
Keywords: DNA Testing; Biological Samples; Social Function; Human Body; Reasonableness